Znanja, veščine in kompetence za urejanje prostora - Temeljotov Salaj, Alenka (Urbani izziv, 2010)
As a result of scientific and technical progress, as well as the increasing complexity of social processes, there is a need for interdisciplinarity of knowledge, skills and competencies for individuals working in spatial planning. The process of spatial planning requires professional and scientific knowledge from various fields, some more artistically oriented and others related to sociology, engineering and technical studies, and economic and legal studies. Individuals must add to the knowledge obtained during the formal education process with new skills and competences to successfully perform their work. We conducted a survey among experts responsible for spatial planning in Slovenia, with the purpose of recognising these new skills and competences and determining their importance. The results of the survey offer insight into the various fields that experts should be familiar with, their specific competences, innate versus learned skills, and problems they deal with at the workplace. We can only expect to find successful solutions to such problems by studying them with other disciplines. Knowledge and information often emerge from peripheral fields of science that enable the formation of new expert and scientific solutions.
Keywords: knowledge; kompetence; prostorsko planiranje; prostorsko urejanje; spatial planning; znanje